Tornabenea ribeirensis (Apiaceaeb a new species from São Nicolau, Cape Verde Islands (West Africa) - Schmidt, K H (1999)
Many species of Apiaceae are found in the Macaronesien Region. Several have been introduccd by human activities, but a number of taxa is endemic to the different archipelagos or even rrstrictcd to a single island. The following enumeration is based mainly on HANSEN & SUNDING ( 1993). In the Arores 28 different taxa of Apiaceae occur; among them four endemic species [AUIMI; hrrrrii WATSON, A. trifoliatum (WATSON) TKEL., Clrtrc~,y~l~~ll~r~~~ cl:oricrm TREL.. SOErich trwrictr GUTIINICK ex SEUB.]. In Madeira the Apiaceae are very diverse and consist ol’ 29 species and subspecies. From the archipelago two monotypic genera, rC/c/trtio. velitru~rr t/ccipicvr.s (SCHRAD. & J. C. WENDL.) Ho~+hl. md kJorli:ia edu[is LOWE and ~hrcc cndcmic species [Oemmrlre diwricore (R. BR.) MABB.. I/nperrr/orio lotvei COSS. and Burrirr~r hre~$~lirrnr LOWE] are described. The Canary Islands have the highest numbcr of plant-species and a high level of endemism. 5-l taxa of Apiaceae are recorded including three endemic genera (Rtrrheopsis A. HANSEX & KUNKEL, Todm-oa PARL. and Tiqyrmm PARL.) and further I5 endemic taxa. The Apiaceae are represented in the Cape Verde Islands by I2 species. Most of the taxa have been introduced by human activities (LOBIN & ZIZKA 1957) like Amvhm grm’eo- 1efr.s L., Apirm grmvolerrs L, Foerricrrhrr urlgore MILL.. Corimrtlru~t~ srrtirvrrrr L. or Petrosilerrm crisprrm (FRILL.) A.W.HILL. These species are cultivated and some of them later became \\esdy. Other species like Ciclosper- UWL /e/~fo/~/l~ll~rrtr (PER%) SPRAGUE (= Apimr leproplr~llrr~rr) are weeds of cultivated grounds or wasted lands. All these species are today widespread in temperate. subtropical or tropical regions all over the world. The only native species are to be found in the endemic genus To~wI~~I~~~ PARL.